Further effects of electromechanically assisted gait trainer (Exowalk®) in patients with chronic stroke: A randomized controlled trial - Yeon-Gyo Nam; Jin Woo Park; Ho Jun Lee; Ki Yeun Nam; Myong Ryol Choi; Chang Seon Yu; Liguo Zhu; Xu Zhang; Jin Won Lee; Bum Sun Kwon (Medical Journals Sweden, 2020)
Objective: To assess the effect on walking ability of electromechanically assisted gait training with a gait trainer (Exowalk®) for patients with chronic stroke. Design: Randomized controlled trial. Subjects: Forty patients with hemiplegia after stroke. Methods: Patients were randomly assigned to control and experimental groups. The control group underwent physical therapist-assisted gait training and the experimental group underwent electromechanically assisted gait training. Interventions were provided for 60 min, 5 days a week, for a period of 2 weeks. Primary outcome was change in Functional Ambulatory Category. Secondary outcomes were walking speed, walking capacity, leg muscle strength and balance. All outcomes were measured before and after the intervention. Results: Although the Functional Ambulatory Category improved significantly after gait training in both groups, the change in Functional Ambulatory Category did not differ between groups. In both groups most secondary outcomes also improved after gait training, but the changes in secondary outcomes did not differ between groups. Conclusion: In patients with chronic stroke, walking improved after gait training with or without electromechanical assistance. Electromechanically assisted gait training was not superior to conventional physiotherapy.